What makes a good school? - Bonnor, Chris (New South, 2012)
How much of what you hear about schools can you trust? Can you believe the marketing hype about unsurpassed facilities, genius teachers and stellar academic achievement? Do you listen to neighbourhood gossip about your local school? Are government statistics the answer? School choice has become one of the most agonising issues of parenthood. Chris Bonnor and Jane Caro have no magic formula, and agree that complex factors come together to make a good school. But drawing on their own experiences and knowledge as school principal, parents and advocates they give parents the tools to do homework a.